Priority of Maintenance of Structural and Architectural Elements Using the Analytical Hierarchy Process (AHP) Method - Fadli Idris; Astiah Amir; Aris Marisa (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2023)
The building construction will decrease with an increased service life of the structure. The school building for SMP Negeri 2 Meulaboh West Aceh is one of the school buildings that need attention from the government. Much of the building damage is due to age and improper maintenance methods. This study aimed to determine the maintenance priorities of the structural and architectural elements of the SMP Negeri 2 Meulaboh school building. This study used the descriptive qualitative method. Primary data was collected through surveys, interviews, documentation, and distributing questionnaires, while secondary data was collected from related institutions or agencies. Data analysis was processed using the Analytical Hierarchy Process (AHP) method. The selection of sample respondents is not random/nonrandom sampling but is carried out using purposive sampling. The analysis results of the order of priority for the maintenance of structural elements the priority, namely, the column, the type of damage to the chipped concrete cover gets the highest priority with a priority value of 0.359. While the second priority is for architectural elements, namely ceilings, walls, doors, windows, and floors, the damage to fading ceiling paint gets the lowest priority with a value of 0.016.